Type 2 Diabetes and Osteoporosis: A Guide to Optimal Management - Paschou, Stavroula Α; Dede, Anastasia D; Anagnostis, Panagiotis G; Vryonidou, Andromachi; Morganstein, Daniel; Goulis, Dimitrios G (The journal of clinical endocrinology and metabolism, 2017)
ContextBoth type 2 diabetes (T2D) and osteoporosis are affected by aging and quite often coexist. Furthermore, the fracture risk in patients with T2D is increased. The aim of this article is to review updated information on osteoporosis and fracture risk in patients with T2D, to discuss the effects of diabetes treatment on bone metabolism, as well as the effect of antiosteoporotic medications on the incidence and control of T2D, and to provide a personalized guide to the optimal management.Evidence AcquisitionA systematic literature search for human studies was conducted in three electronic databases (PubMed, Cochrane, and EMBASE) until March 2017. Regarding recommendations, we adopted the grading system introduced by the American College of Physicians.Evidence SynthesisThe results are presented in systematic tables. Healthy diet and physical exercise are very important for the prevention and treatment of both entities. Metformin, sulfonylureas, dipeptidyl peptidase-4 inhibitors, and glucagon-like peptide-1 receptor agonists should be preferred for the treatment of T2D in these patients, whereas strict targets should be avoided for the fear of hypoglycemia, falls, and fractures. Insulin should be used with caution and with careful measures to avoid hypoglycemia. Thiazolidinediones and canagliflozin should be avoided, whereas other sodium-dependent glucose transporter 2 inhibitors are less well-validated options. Insulin therapy is the preferred method for achieving glycemic control in hospitalized patients with T2D and fractures. The treatment and monitoring of osteoporosis should be continued without important amendments because of the presence of T2D.ConclusionsPatients with coexisting T2D and osteoporosis should be managed in an optimal way according to scientific evidence.We systematically reviewed the literature for human studies regarding the effects of type 2 diabetes treatment on osteoporosis and the opposite. We provide a personalized guide to optimal management.